Messages from Frank's Landing : a story of salmon, treaties, and the Indian way - Wilkinson, Charles F., 1941- (University of Washington Press, 2000)
Explores the historical, legal, and social context of Indian fishing rights in the Pacific Northwest, focusing on the efforts of Billy Frank Jr. and his family to restore and preserve the Native American way of life.